Worksite Prevalence of (un)Diagnosed Cardiovascular Risk Factors From a Health-Check-Program in An Austrian Company. Issue 12 (December 2015) - Luger, Maria; Luger, Eva; Höfler, Jürgen; Dämon, Sabine; Angelmaier, Lukas; Maschke, Katharina; Rittmannsberger, Barbara; Sakho, Christoph; Pfeiffenberger, Albert; Schätzer, Manuel; Schmidjell, Walter; Lechleitner, Monika; et al.
Abstract : Objective: This investigation aims to determine cardiovascular disease risk profile in a cohort of employees. Methods: In 704 participants, within the Special Institute for Preventive Cardiology And Nutrition health-check-program, body mass index, waist circumference, blood pressure (BP), lipids, glucose, and 10-year cardiovascular disease risk were assessed. Results: Mean age was 37 (10) years (20% women) with 25.5 (3.9) kg/m 2 . A total of 38% demonstrated overweight, 44% abdominal obesity, 12% obesity, and 19% metabolic syndrome. We found a significant difference in increased BP versus diagnosed hypertension (47% vs 14%; P < 0.001). Increasing age was a significant predictor of metabolic syndrome (odds ratio [95% confidence interval] = 1.08 [1.06 to 1.10]; P < 0.001). Ten percent had intermediate and 8% high cardiovascular disease risk. A total of 79% demonstrated at least one risk factor. Conclusions: We detected high prevalence of risk factors particularly increased BP and abdominal obesity. Workplace prevention programs should aim in initially identifying risk factors and subsequently improving lifestyle.